Inter-relações da produtividade de cana soca com a resistência à penetração, umidade e matéria orgânica do solo - Dalchiavon, Flávio Carlos; Carvalho, Morel De Passos E [UNESP]; Montanari, Rafael [UNESP]; Andreotti, Marcelo [UNESP]; Bem, Edjair Augusto Dal [UNESP] (Universidade Federal de Viçosa (UFV), 2014)
The sugarcane crop plays an important role on Brazilian economy,, especially in the aspect related to alternative energy sources. Yield of ratoon cane (2nd cycle) was evaluated in relation to resistance to penetration, gravimetric moisture and organic matter in a Typic Tropustalf, in the municipality of Suzanápolis (SP), 20º28'10'' S and 50º49'20'' W, in the Brazilian cerrado, in 2009. The main purpose was to select, among the attributes surveyed, the one with the highest linear and spatial correlations that explains the variability of sugar cane yield. A geostatistical grid was installed in order to collect data from the soil as well from the plant, with 120 sampling points in an area of 14.53 ha. Organic matter correlated linearly and negatively with penetration resistance, indicating that the soil management practices that aim its increase in the soil profile can improve soil physical conditions, and consequently, the development and yield of sugarcane. Both gravimetric moisture (UG) and content of soil organic matter (OM) correlated directly, linearly (UG2 and MO1) and spatially (UG1 and MO1) with sugarcane yield, proving to be the best attributes, among the evaluated ones, to estimate and increase the sugarcane yield.

A cultura da cana-de-açúcar desempenha, sobretudo no aspecto relacionado às fontes energéticas alternativas, importantíssimo papel. No ano de 2009, no município de Suzanápolis (SP), cujas coordenadas são 20º 28' 10'' S e 50º 49' 20'' W, no cerrado brasileiro foi analisada a produtividade da cana soca (2º ciclo) em razão da resistência à penetração, umidade gravimétrica e matéria orgânica de um Argissolo Vermelho eutrófico. O objetivo foi selecionar, entre os atributos pesquisados, aquele com a melhor correlação, a linear e a espacial, para explicar a variabilidade da produtividade da cana-de-açúcar. Foi instalada a malha geoestatística para a coleta de dados do solo e da planta, com 120 pontos amostrais, numa área de 14,53 ha. A matéria orgânica correlaciona-se linear e negativamente com a resistência à penetração, indicando que manejos do solo que visem seu aumento no perfil melhoram suas condições físicas e, por conseguinte, o desenvolvimento e a produtividade da cana-de-açúcar. A umidade gravimétrica (UG) e o teor de matéria orgânica do solo (MO) correlacionam-se direta, linear (UG2 e MO1) e espacialmente (UG1 e MO1) com a produtividade da cana-de-açúcar, demonstrando serem os melhores atributos, dentre os pesquisados, para estimar e aumentar a produtividade agrícola da cana-de-açúcar.
Relationship of sugarcane ratoon yeld with resistance penetration, humidity and soil organic matter
Keywords: geoestatística; manejo e conservação do solo; Saccharum spp.; variabilidade espacial; geostatistical; soil management and conservation; Saccharum spp.; spatial variability